Behavioral, sociodemographic, and clinical factors associated with hospital costs following road traffic injuries in Colombia - Sandra Milena Zuleta Alarcón; Anderson Bermon Angarita; Alejandra Mendoza-Monsalve (Frontiers in Public Health, 2026)
Background Road traffic injuries are a major public health and economic burden, particularly in low- and middle-income countries, where increasing motorization and limited trauma system capacity contribute to healthcare expenditures. Evidence on factors associated with hospital costs in Latin America remains limited. Objective To evaluate sociodemographic, accident-related, and clinical complexity factors associated with hospital costs among patients with traffic-related injuries treated at a Colombian referral hospital. Methods A retrospective cohort study included patients treated for road traffic injuries between 2016 and 2025 at a high-complexity referral center in Colombia. Hospital costs were expressed in Colombian pesos (COP). Multivariable linear regression using logarithmically transformed costs was performed. Results A total of 13,899 patients were included. Median age was 32 years (IQR 25–43), and 64.0% were male. Motorcycles were involved in 87.1% of accidents. Median hospital cost was COP 431,300 (IQR 190,071–1,524,400). Surgical intervention was associated with the greatest increase in costs (1,502.6%), followed by ICU admission (1,063.2%) and each additional hospital day (6.8%). Early-morning accidents were associated with 46.8% higher costs, while nighttime crashes showed a 19.3% increase. Male sex and selected occupational categories were also associated with higher costs. After adjustment for clinical complexity markers, most geographic differences were attenuated. Conclusion Hospital costs following road traffic injuries were mainly associated with clinical complexity markers, particularly surgery, ICU admission, and hospital length of stay. Early-morning crashes and selected sociodemographic factors were also associated with increased costs.